Student Learning Difficulties in Middle School Science Learning During the Covid-19 Pandemic: A Case Study in the Teminabuan District, South Sorong Regency - Annisa Luxfiati Wugaje; Febrian Andi Hidayat; Abdul Rachman Tiro; Supriyadi (CV. Dharma Samakta Edukhatulistiwa, 2023)
The objective of this research is to investigate the challenges faced by junior high school students in comprehending Science educations (IPA) in Teminabuan District, South Sorong Regency amidst the Covid-19 pandemic. The present investigation employs a survey methodology utilizing a qualitative descriptive framework and case study analyses. The participants of this investigation were pupils enrolled in three junior high schools located in the Teminabuan District, specifically Teminabuan 1 Public Middle School, Teminabuan 2 Public Middle School, and Teminabuan Yapis Middle School. The methodology employed in this research involves the utilization of a questionnaire and documentation as the primary means of data collection. The process of data analysis involves the collection and examination of data obtained from questionnaires and documentation. The findings of the investigation into the proportion of participants' responses to a survey on the challenges encountered by students in comprehending science at the junior high school level, consisting of twenty queries responded to by ten student participants, indicated that the majority of the respondents experienced learning difficulties in the uppermost classification. This suggests that junior high school students encounter challenges in comprehending science subjects. The present study elucidates the challenges encountered by junior high school students in comprehending science education amidst the Covid-19 pandemic. The present study makes a valuable contribution to the advancement of pedagogical approaches that are better suited to addressing the challenges posed by the COVID-19 pandemic in the context of science education.